Establishment of the colloidal chitin enzymatic hydrolysis conditions to obtain N-acetyl glucosamine - Rivera-Solís, Rodrigo A.; Granados-Baeza, Manuel J.; Solís-Pereira, Sara E.; Lizama-Uc, Gabriel; Magaña-Ortiz, Denis; Sánchez-González, Mónica N.; Rojas-Herrera, Rafael A.; Rivera-Muñoz, Gerardo (Frontiers in Sustainable Food Systems, 2023)
The wastes generated by the shrimp industry are approximately between 50 and 60% of the catch volume. These residues such as head, viscera, and shell are potential pollutants if they are not treated for proper disposal. One way to solve this problem is to use the residues as functional food ingredients. In this regard, shrimp residues are rich in chitin, the second most abundant biopolymer on the planet after cellulose. Chitin is composed of N-acetyl glucosamine, a molecule used as a sweetener in the food industry and as an aid in the treatment of coronary diseases and gonarthrosis. N-acetyl glucosamine can be obtained by the hydrolysis of colloidal chitin using chemical or enzymatic methods; however, chemical methods are associated with pollution. In this study, we determined the hydrolysis conditions of shrimp colloidal chitin for obtaining N-acetyl glucosamine, using the extracellular enzymes produced by a marine bacterium isolated in the coastal zone of Progreso, Yucatan, Mexico. The best N-acetyl glucosamine yield obtained was 2.65%, using 10 mg/mL colloidal chitin, at 60°C, and pH 8.9 with 3.5% NaCl.